PURWARUPA SISTEM PAKAR DENGAN METODE KETIDAKPASTIAN FUZZY MAMDANI PRODUCT UNTUK MENENTUKAN MENU HARIAN PENDERITA DIABETES MELITUS (Studi Kasus: RS. Dr. Soetarto Yogyakarta) - , NUR HASANAH; , Drs. Retantyo Wardoyo, M.Sc., Ph.D, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
It is predicted that 12.4 million people will suffer from Diabetes Mellitus (DM) in Indonesia in 2025, the fifth biggest number in the world. Menu planning is one of the important aspects in DM management. Expert system can be used as a consultant that gives suggestion to users as well as an assistant for experts. Fuzzy logic is flexible, has the ability in linguistic reasoning and can model complex mathemathical functions. This research aims to implement fuzzy logic uncertainty method into expert sistem prototype to determine diabetic daily menu based on daily calorie needs. The advantage is to find out the accuracy of Mamdani Product inference engine. The knowledge-based approach in this expert system uses Rule-Based Reasoning. The inference process employs fuzzy logic making use of Mamdani Product inference engine. The fuzzifier used is Singleton while defuzzifier is Center Average. The produced expert system can be used to determine diabetic menu. The combination of Singleton fuzzifier, Mamdani Product inference engine and Center Average defuzzifier that is used in expert system can be applied in the domain of the problem under discussion.